Life Everlasting? The Absurdity of Perpetual Privilege - Dryden, Jean (Archivaria)

(untitled) (Association of Canadian Archivists, 2025)
This article looks at solicitor-client privilege and the lawyers’ duty of confidentiality from the perspective of the harm done to legal history and Canada’s documentary heritage by the claim that privilege never ends. After discussing the emergence of the field of legal history, the scarcity of lawyers’ papers preserved in archives, and efforts to address the perpetual privilege problem, the author examines the rationales for privilege and the justifications for its purportedly absolute and unending nature and finds them wanting. The article then sets out the role of archival institutions in preserving historically valuable records and making them available for research. The author argues that, after a reasonable interval, the public interest in access to lawyers’ papers trumps privilege and that archivists have the tools and experience to manage (temporary) access restrictions to such materials. The recent guidelines on disclosure of historical records under the Access to Information Act signal that privilege need not be perpetual and indicate the need to start a conversation to finally resolve the conflict between privilege and fuller documentation of both the legal profession and its impact on society.